Examining the Impact of House Size on Building Embodied Energy - Abdul Rauf; Daniel Euroizing Attoye; Malik Mansoor Ali Khalfan; Muhammad Tariq Shafiq (Buildings)
The effects of buildings on the environment can be reduced with research-based alternative building designs. This study focuses on reducing the building space to lower the overall size of a building as a strategy to reduce the building’s embodied energy. The aim of this study was to investigate the initial embodied energy (IEE) of a residential building that was systematically reduced in size. Using input–output-based hybrid analysis, the IEE for three architecturally distinct four-bedroom residential prototypes (P1, P2, and P3) was calculated. The IEE for P1 (525 m2), P2 (266 m2), and P3 (109 m2) were 3555, 2008, and 1000 GJ, respectively. This indicates a 72% reduction in embodied energy consumption when the largest prototype (P1) was transitioned to the smallest (P3). When analyzing IEE/m2 and IEE/m2/occupant, it becomes apparent that larger spaces tend to have a lower IEE/m2. However, when the occupancy increases, the IEE/m2/occupant decreases by 25–33%. Therefore, considering occupant-centered design for residential buildings, the benefits of a large house are not justifiable. These findings can help inform decisions regarding the optimization of residential spaces to minimize environmental impacts.